Critical Theory And Accounting Research: A Critical Review - Irsyadillah Irsyadillah (Proceedings of AICS - Social Sciences, 2016)
This paper is concerned with providing a literature review regarding the use of critical theory in accounting research. In Indonesian context, critical theory has not commonly used to study accounting issues. The fact that both accounting practice and accounting education continue to be undermined by a single prevailing worldview coming from Anglo-American capitalism promoting maximizing shareholder value. The paper argued that given the underlying context of accounting, critical theory is so important to be adopted in order to be able to challenge the prevailing dominant paradigm and at the same time providing alternative perspective. The alternative could be even developed according to indigenous cultural and ethical values. More importanly, critical theory is about providing liberation and emancipation including in the area of accounting.